DECIPHERING THE COMPLEXITIES AND UNCERTAINTIES IN PUBLIC SCHOOLS IN THE UNITED STATES - Benjamin DAMOAH; Samuel OWUSU; Clement YEBOAH; Andrews ACQUAH; Daniel PAINTSIL (Social Sciences and Education Research Review)
This literature review paper sheds light on the systemic deficiencies, complexities, and untold stories in the public school system in the United States. It reveals that despite being an advanced democracy and a first-world country, the US education system still faces issues that hinder its developmental trajectory. Surprisingly, the uncertainties unmasked in the US education system are not far-fetched from the experiences that persist in developing countries. The paper is thought-provoking and raises important questions about the state of education in the modern world. As a result, relevant literature was thematically reviewed on systemic disparities that hinder the growth and development of education. The findings of the paper among others discussed issues that include the quantification of educational outcomes, systemic inequality, and segregation, school funding, differential access to infrastructure resources, as well as teachers' competencies and retention. Addressing the complexities and uncertainties of public education requires a multi-faceted approach involving policymakers, educators, parents, and communities to ensure equity and efficacy.